1975
DOI: 10.1111/j.1476-5381.1975.tb07577.x
|View full text |Cite
|
Sign up to set email alerts
|

Decamethonium in the Perfused and Immersed Rat Diaphragm

Abstract: 1 The water content and mannitol space of rat diaphragms which were perfused through the inferior vena cava was increased compared with immersed diaphragms. The potassium content of both preparations, when expressed in terms of dry weight, was maintained at similar values to that found in vivo. 2 Despite the application of a constant concentration of decamethonium, a steady level of neuromuscular block was not obtained in either the perfused or immersed rat diaphragm. The immersed preparation differed from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Longitudinal sections showed grains all along the fibres, with a concentration in the region of the end-plate and for several hundred microns on either side. There is some indication that decamethonium is entering the cells via the receptor-activated sodium channels; Creese & England (1970) and Humphrey (1975) both found that the permeability of rat muscle to decamethonium was similar to that of sodium and much lower than that of the potassium ion. In addition, tubocurarine prevents both the entry of the drug into the cells and the pharmacological action on the receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal sections showed grains all along the fibres, with a concentration in the region of the end-plate and for several hundred microns on either side. There is some indication that decamethonium is entering the cells via the receptor-activated sodium channels; Creese & England (1970) and Humphrey (1975) both found that the permeability of rat muscle to decamethonium was similar to that of sodium and much lower than that of the potassium ion. In addition, tubocurarine prevents both the entry of the drug into the cells and the pharmacological action on the receptors.…”
Section: Discussionmentioning
confidence: 99%